Creating by recycling - Llimós, Anna.; Giralt, Nuria; Sadurni, Laia.; Nos y Soto (Woodbridge, CT : Blackbirch Press, 2000)
Provides instructions for a variety of craft projects using such recycled items as foam trays, empty soda cans, cardboard tubes, plastic bottles, and pieces of cloth.
Translation of: Crea y recicla.
Includes bibliographical references (p. 31) and index.
5.0.
5.0
3-6
Keywords: Handicraft -- Juvenile literature; Plastic bottle craft -- Juvenile literature; Recycling (Waste, etc.) -- Juvenile literature; Handicraft; Recycling (Waste, etc.); Handicraft; Recycling